Wanita 74 Tahun Dengan Metastasis Pada Lobus Parieto-Oksipital Pada Melanoma Maligna - Pussof Yayazucah Titanic; Timotius Timotius; Johansen Johansen; Given Kentanto; Teguh Priyanto (Jurnal Ners, 2023)
Melanoma is a tumor that is produced by the malignant transformation of melanocyte cells. Melanoma is the leading cause of premature death from cancer. Known risk factors include personal or family history of melanoma, large numbers of naevi and/or dysplastic naevi, congenital melanocytic naevi, sun-damaged skin, history of non-melanoma skin cancer, and immunodeficiency. Based on the Basic Health Research Results (Riskesdas) report, skin cancer as a whole ranks 3rd in Indonesia. Epidemiological studies of skin cancer have reported in Jakarta in 2014–2017, where out of 263 cases of skin cancer, malignant melanoma ranks third with the highest incidence of skin cancer (5.7%). Diagnosis of melanoma can be made by assessing the skin lesions with the naked eye and also by the patient's clinical symptoms. A person's risk of metastases is directly related to the depth of invasion and ulceration of their primary lesion. Among solid tumors, melanoma has one of the highest propensities to cause brain metastases with a proportion of more than 25% of patients. Although the current cancer treatment paradigm may reflect a combination of surgery, chemotherapy, radiotherapy, and immunotherapy with medical management, options for the treatment of metastatic brain cancer remain limited.